Method for Total Air Flow Prediction in Compartment. A Numerical Study of the Climate System at Volvo Car Corporation. - Svensson, Martin (My University, 2014)
To predict and control the total amount of air passing through the ventilation system is of great importance when designing and developing climate systems for the automotive industry. There are clear benfits both concerning the climate comfort in the compartment and cost efficiency in the development process, if the flow in an early stage can be estimated and analysed virtually. This project is a part of the development work of a computational method to be used for flow rate prediction of the climate system in the automotive industry at the Volvo Car Corporation (VCC). The new method consists of guidelines for setting up a numerical model of the climate system and directives on how to carry out the flow rate computations. The climate system refers to the complete internal system for transporting air through the vehicle compartment. In this thesis however, a model of the VCC climate test rig was used instead of a complete car model in order to simplify the verfication.
Keywords: Energi; Termisk energiteknik; Hållbar utveckling; Strömningsmekanik; Transport; Energy; Thermal energy engineering; Sustainable Development; Fluid mechanics; Transport